ETHICAL STANDARDS AND PHOTOGRAPHY IN NEWSPAPERS - Marija; Mitrović, Marta (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Newspaper photography is a very common and important media content that initially attracts the attention of readers and thus influences their opinions about the events depicted. The study of the visual in the media is becoming increasingly important in media theory. Visual content is becoming more dominant because it can convey a lot of information efficiently due to the absence of language barriers. This is why adherence to professional standards in the publication of newspaper photographs is so important. The only document that regulates the ethical standards of newspaper photography in Serbia is the Code of Journalists, but it is not legally binding on the editorial policy of the media. The consequences of violating its provisions are public warnings issued by the independent self-regulatory body, the Press Council. The results of a quantitative and qualitative analysis of newspaper photos published in three daily newspapers (the broadsheet Politika, the semi-tabloid Blic and the tabloid Kurir) has shown to what extent the ethical standards are respected in practice. The research was conducted in the first week of April 2023. The analysis included all photos published during this period, with the exception of advertising photos. In the paper, the analysis of newspaper photos included the following categories defined by the Code: whether the difference between a documentary photograph and a photoshopped image is precise; whether the illustrative role of the photo is emphasized when it is not taken directly at the scene of the event; whether the source/authorship of the photo is indicated; whether the principle of presumption of innocence applies and the privacy and identity of the victim or suspect are respected (by not publishing photos, among other things), even if he pleads guilty, until a court verdict is pronounced; whether the published photos were taken with hidden cameras; and whether the photos contain inappropriate, disturbing and pornographic content. The hypothesis on which the article is based is that ethical standards are not fully met in the newspapers studied, that there are more ethical violations in the semi-tabloid and tabloid newspapers, with failure to credit the source or authorship of the photo and disregard for the presumption of innocence and the right to privacy being the most common.